MAC improvements for very high throughput WLANs. (2019) - Vijay, B.T.; Malarkodi, B.
Here we present the first amendments of high throughput networks identified as IEEE 802.11n originated in 2009 to achieve 150 Mbps speed for typical wireless systems to provide better wireless technology. At the same time, to further improve the medium access control (MAC) throughput, a pair of new amendments for WLAN standard are developed which are IEEE 802.11ac and IEEE 802.11ad. The 802.11ac is designed to achieve 1.3 Gbps speed due to its larger frame sizes, improved queuing and enhance the quality of service (QoS) features with the help of multi-user MIMO. The 802.11ad is designed to allow around 7 Gbps while using the possibility of transmitting in the 60 GHz band that can offer the chance to get the high gain and fewer interference features of directional antennas. Lastly, simulation results show the study of QoS requirements for interactive multimedia transport flow is readily achievable in 802.11ac/ad when compared to 802.11n and other legacy standards.